(untitled) (Baghdad Science Journal, 2019)
Fusobacterium are compulsory anaerobic gram-negative bacteria, long thin with pointed ends, it causes several illnesses to humans like pocket lesion gingivitis and periodontal disease; therefore our study is constructed on molecular identification and detection of the fadA gene which is responsible for bacterial biofilm formation. In this study, 10.2% Fusobacterium spp. were isolated from pocket lesion gingivitis. The isolates underwent identification depending on several tests under anaerobic conditions and biochemical reactions. All isolates were sensitive to Imipenem (IPM10) 42.7mm/disk, Ciprofloxacin (CIP10) 27.2mm/disk and Erythromycin (E15) 25mm/disk, respectively. 100% of Fusobacterium spp. isolates had 16S rDNA gene (360bp.), whereas two isolates had fadA gene (232bp.)